Urethane Improves the Response of Auditory Neurons to Tone - Huang, Bowan; Yan, Linqing; Li, Yan; Liu, Wenhui; Liu, Manhua; Xiao, Zhongju; Huang, Jinping (Frontiers in Cellular Neuroscience, 2022)
Urethane has little effect on nervous system and is often used in neuroscience studies. However, the effect of urethane in neurons is not thoroughly clear. In this study, we investigated changes in neuron responses to tones in inferior colliculus during urethane anesthesia. As urethane was metabolized, the best and characteristic frequencies did not obviously change, but the minimal threshold (MT) remained relatively stable or was elevated. The frequency tuning bandwidth at 60 dB SPL (BW60 dB SPL) remained unchanged or decreased, and the average evoked spike of effective frequencies at 60 dB SPL (ES60 dB SPL) gradually decreased. Although the average evoked spike of effective frequencies at a tone intensity of 20 dB SPL above MT (ES20 dB SPL above MT) decreased, the frequency tuning bandwidth at a tone intensity of 20 dB SPL above MT (BW20 dB SPL above MT) did not change. In addition, the changes in MT, ES60 dB SPL , BW60 dB SPL and ES20 dB SPL above MT increased with the MT in pre-anesthesia awake state (MTpre-anesthesia awake). In some neurons, the MT was lower, BW60 dB SPL was broader, and ES60 dB SPL and ES20 dB SPL above MT were higher in urethane anesthesia state than in pre-anesthesia awake state. During anesthesia, the inhibitory effect of urethane reduced the ES20 dB SPL above MT, but did not change the MT, characteristic frequency, or BW20 dB SPL above MT. In the recording session with the strongest neuron response, the first spike latency did not decrease, and the spontaneous spike did not increase. Therefore, we conclude that urethane can reduce/not change the MT, increase the evoked spike, or broaden/not change the frequency tuning range, and eventually improve the response of auditory neurons to tone with or without "pushing down" the tonal receptive field in thresholding model. The improved effect increases with the MTpre-anesthesia awake of neurons. The changes induced by the inhibitory and improved effects of urethane abide by similar regularities, but the change directions are contrary. The improvement mechanism may be likely due to the increase in the ratio of excitatory/inhibitory postsynaptic inputs to neurons.